Midpalatal suture maturation stage assessment in adolescents and young adults using cone-beam computed tomography - Ludy Marileidy Jimenez-Valdivia; Violeta Malpartida-Carrillo; Yalil Augusto Rodríguez-Cárdenas; Heraldo Luis Dias-Da Silveira; Luis Ernesto Arriola-Guillén (SpringerOpen, 2019)
Abstract Background The aim of this study was to evaluate the midpalatal suture maturation stages in adolescents and young adults using cone-beam computed tomography (CBCT). Methods The sample comprised 200 CBCT scans of individuals aged 10 to 25 years old (95 males and 105 females) divided into three groups, adolescents (n = 48), post-adolescents (n = 52), and young adults (n = 100). The Planmeca ProMax 3D software was used for the midpalatal suture maturation stage evaluation according to Angieleri's method, using cross-sectional axial slice. Two previously calibrated examiners analyzed the images and classified according to five different maturation stages. A, B, and C stages were considered with open midpalatal suture, and D and E were considered without open midpalatal suture. Association tests were performed using chi-square test also, and a binary logistic regression was evaluated (P < 0.05). Results The possibility to find open midpalatal suture in individuals of 10 to 15 years old was 70.8%, in subject aged 16 to 20 and 21 to 25 years old was 21.2% and 17%, respectively. Furthermore, this possibility in individuals older than 16 years was greater in males than in females. Conclusions The possibility to find open midpalatal suture in post-adolescents and young adults is greater than the orthodontists considered years ago. Furthermore, men are more likely to find midpalatal suture opening. These implications might be considered by the orthodontists when maxillary expansion is required. Besides, the ossification of the middle palatal suture is very variable, and therefore, the use of CBCT might be recommended to clarify this possibility.